Evaluasi Program Ekstrakurikuler Olahraga Sekolah Dasar Menggunakan Model CIPP - Aditya Rachmat; Asep Angga Permadi; Zaenal Arifin (Jurnal Porkes, 2026)
The implementation of extracurricular sports programs in elementary schools is often hindered by limited facilities and resources in rural areas, which results in suboptimal development of students’ talents. This study aims to evaluate the effectiveness of extracurricular sports programs in elementary schools by focusing on an analysis of the context, input, process, and product components using the CIPP model. This qualitative study with a case study design involved school principals, supervising teachers, and students selected through purposive sampling. Data collection was conducted through in-depth interviews, participatory observation, and document analysis, while data analysis utilized the Miles and Huberman interactive model. The findings indicate that the context and product aspects were rated as good due to the program’s high relevance to students’ needs and its success in fostering discipline and sportsmanship. Conversely, the input and process aspects were deemed suboptimal due to limited standard facilities, uncertified coaches, and monotonous training methods lacking written plans. This study concludes that the sports extracurricular program in rural elementary schools is successful in character building but weak in achieving competitive performance; therefore, synergy between schools and local governments is needed to increase the budget allocation for sports infrastructure and facilitate the improvement of coaches’ competencies.